THE INFLUENCE OF EMPLOYEE COMPETENCE, WORK CULTURE AND WORK FACILITIES ON SERVICE QUALITY AT PUSKESMAS KECAMATAN TAMAN SARI KOTA ADMINISTRATION, WEST JAKARTA - Mabruri; Paisal Halim (JILPR Journal Indonesia Law and Policy Review, 2023)
Public service is the responsibility of the government which is mandated by the 1945 Constitution and is carried out by all central and regional government agencies. Public service is a form of embodiment of the function of the state apparatus in providing welfare and meeting the needs of the community. Health development held at the Puskesmas which was echoed in Permenkes No. 43 of 2019. Adequate health services are the foundation of the community and become one of the basic needs besides food and education. The Taman Sari District Health Center as a regional work unit of the DKI Jakarta Provincial Health Office generally provides preventive, promotive, curative and rehabilitative health services. The purpose of this study was to analyze and evaluate the effect of employee competence, work culture and work facilities on service quality at Taman Sari Health Center. The research method was causality research with a quantitative approach. The type of data used in this study uses primary data collection. The data received in the questionnaire is in the form of ordinal data. The population in this study were workers at the Taman Sari District Health Center, which amounted to 120 people. This research uses probability sampling technique in taking samples by random sampling. Determination of the sample size is done by the Slovin method. The standard error is 10%. The results of this study partially show that employee competence has an effect of 11.5%, work culture has an effect of 24.8% and work facilities have an effect of 46.9% on service quality and simultaneously variables of employee competence, work facilities and work culture are influenced by 83,2% and the rest is influenced by other variables outside the study.